Teachers and Islamic Education in Sharia Studies - Ulum, Miftachul; Mun'im, Abdul (Journal of Islamic Education, 2023)
This research aims to examine a teacher from the perspective of studying the interpretation of the Al-Qur'an. The method in this research is descriptive, namely by providing a description of the research object. The research results can be explained that the first educator is Allah SWT, the second educator is the Prophet Muhammad SAW, and the third educator is parents. The task of educators has a purifying function, meaning as self-preserver, developer and maintainer of human nature. The function of teaching, meaning as a transmitter of knowledge and various beliefs to the public so that they apply all their knowledge in life